La Alianza del Pacífico y los efectos políticos de la interdependencia económica - Morales Giraldo, Juan Francisco (2017)
The purpose of this paper is to analyze the unintended political effects of economic interdependence among South American members of the Alliance of the Pacific by tracing the evolution of their mutual trade in relation to the intensity of their military competitive dynamics from 2001 to 2015. Two measurement instruments are use: an intra-regional trade index based on commerce data, and a coordination index based on arms purchases. The question is if the formation of the Alliance and trade relations now embedded in it have had any effect on the cooperation-conflict political balance. Issues concerning the method are discuss as well as the implications of the research for the intertheory debate. Last section is dedicate to discuss briefly the historical understanding of regional conflicts and normative aims of regional integration.